Pelatihan Penggunaan Social Media Marketing - Dinda Ayu Andini; Edy Purwanto; M. Munir Syam AR (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2022)
The advancement of digital technology today is a great opportunity for entrepreneurs to be able to market their products easily. This community service was carried out for employees of Bang Alief Bangselok Sumenep. This activity is carried out by providing socialization and training on the use of social media marketing. This activity consists of several stages, namely the preparation stage, the activity implementation stage, and the last stage is the activity evaluation stage. From the results of the training that has been carried out, information is obtained on the level of understanding of the participants on the training material provided. And, it can be concluded that the training on the use of social media for Bang Alief Bangselok Sumenep employees that has been carried out, can increase the ability of employees to use Instagram-based social media and create accounts and manage social media as a medium for promoting their service businesses